Religiusitas dan konsep kebahagiaan tokoh utama dalam novel “Cinta dalam Sujudku” karya Diana Febi (kajian psikologi positif Martin Seligman) - Zhoafir, Muhammad (Maliki Interdisciplinary Journal, 2024)
This study aims to (1) describe religiosity in the novel "Love in Sujudku" (2) describe the concept of happiness of the characters in the novel "Love in Sujudku." (3) describe the correlation between religiosity and the concept of happiness in the novel "Love in Sujudku". The study of religiosity and the concept of happiness in the novel "Love in Sujudku" is studied using Martin Seligman's perspective. This research method uses a qualitative descriptive method with the Miles and Huberman technical model with the stages of data reduction, data display, and drawing conclusions. The data collection technique is read-write. With the object of study in the novel "Love in Sujudku" there are two religious aspects consisting of sincerity to God and resignation. In this novel there are two concepts of happiness (1) the symbol of happiness in the novel "Love in Sujudku." (2) the authenticity of the character's happiness in the novel "Love in my Sujud (3) the correlation of how religion becomes a means to true happiness.